Isometric contraction of the abductor digiti minimi muscle in man - Burke, David (1974)
Isometric contraction of the abductor digiti minimi muscle (ADM) has been studied in six normal subjects. Twitch contraction times of ADM ranged from 60 to 68 ms and twitch torque ranged from 2·33 to 6·24 × 10(-3) Nm. In three subjects torque declined by an average of 31% after tetanization at 50 Hz for 30 seconds but there was no similar diminution in the evoked muscle action potential suggesting that the fatigue arose from intrinsic muscular mechanisms. A marked decline in tetanic torque occurred with continued tetanization in two subjects for a total of five minutes, but this change was accompanied by a decrease in the muscle action potential. In six subjects threshold stimulation to the ulnar nerve at the wrist and to various sites over the motor point of ADM allowed 55 threshold twitch contractions to be identified after averaging. A unimodal range of contraction times ranging from 40-100 ms was found and this was confirmed by additional experiments in two subjects in whom 30 threshold twitch contractions were identified using a needle electrode to stimulate various sites in the motor point. Tetanization at 50 Hz was performed using threshold stimulus levels. Nine threshold tetanic contractions were evoked in two subjects. In eight tetanic torque progressively fatigued to between 14 and 20% within 60-90 seconds, but, in one tetanic contraction, torque proved relatively fatigue resistant. These results suggest that there is a homogeneous group of motor units in ADM (with respect to contraction time) and that this group contains what are probable fast twitch fatigue sensitive and fatigue resistant motor units. No evidence of a distinct group of slow twitch units was found.